Technical Quality of Root Fillings Performed by Dental Students in Babol Dental School - Maryam Ehsani; Farida Abesi; Tania Ghasemi (Mashhad University of Medical Sciences, 2014)
Introduction: There is substantial evidence that the technical quality of root canalfilling has a significant effect on the outcome of root canal treatment. Theaim of this study was to evaluate the technical quality of root canal fillingsperformed by dental students. Methods: The records of 325 teethradiographs, treated by dental students in 2008-2009 in Babol Dental School,were selected and evaluated. For each tooth, three periapical radiographs(before treatment, during operation and at the end of treatment) were examined.Filling length, density and taper, and presence or absence of void wasevaluated. Obturations that have proper length, density and taper, without anyvoid are classified as acceptable root canal fillings. The SPSS statisticalsoftware and Chi-Square test were used for analysis. Results: Of the 325radiographs, 72% had good length and 75% had acceptable taper. There were 14.2%low densities, whereas, only 3.32% of teeth have no void. At least 17.8% ofteeth had underfilling and 10.2% overfilling. Finally, only 17.5% of teethshowed acceptable filling length, taper and density without any void. There wasno significant difference between the 4th and 5th yearstudents and oral hygienist (who studied oral hygiene and now continuing it todentistry) in root canal filling quality (P> 0.05). Conclusion:Technical quality of root fillings performed by dental students was found to beless than 20%. .It should be revised in the endodontic curriculum requirementto improve their performance